Rational design of coagulation factor VIIa variants with substantially increased intrinsic activity - Persson, Egon (The National Academy of Sciences, 2001)
A trace amount of coagulation factor VII (FVII) circulates in the blood in the activated form, FVIIa (EC 3.4.21.21), formed by internal proteolysis. To avoid disseminated thrombus formation, FVIIa remains in a conformation with zymogen-like properties. Association with tissue factor (TF), locally exposed upon vascular injury, is necessary to render FVIIa biologically active and initiate blood clotting. We have designed potent mutants of FVIIa by replacing residues believed to function as determinants for the inherent zymogenicity. The TF-independent rate of factor X activation was dramatically improved, up to about 100-fold faster than that obtained with the wild-type enzyme and close to that of the FVIIa-soluble TF complex. The mutants appear to retain the substrate specificity of the parent enzyme and can be further stimulated by TF. Insights into the mechanism behind the increased activity of the mutants, presumably also pertinent to the TF-induced, allosteric stimulation of FVIIa activity, were obtained by studying their calcium dependence and the accessibility of the N terminus of the protease domain to chemical modification. The FVIIa analogues promise to offer a more efficacious treatment of bleeding episodes especially in hemophiliacs with inhibitory antibodies precluding conventional replacement therapy.